1996
DOI: 10.1007/s0021663560037
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of F:O ratios in rare earth oxide fluorides by energy dispersive X-ray analysis

Abstract: The F:O ratio in homogeneous and inhomogeneous rare earth oxide fluoride systems of compositions RO(1+x)F(1-2x) with -0.1 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
1998
1998

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Marx et al 1996) 1994). In our study, the TEM-EDXS system was calibrated for quantitative analysis by proper reference materials for xylem tissues of latewood tracheids of spruce with an accuracy of 66 to 87 % for Κ and 84 to 87 % for Ca.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marx et al 1996) 1994). In our study, the TEM-EDXS system was calibrated for quantitative analysis by proper reference materials for xylem tissues of latewood tracheids of spruce with an accuracy of 66 to 87 % for Κ and 84 to 87 % for Ca.…”
Section: Discussionmentioning
confidence: 99%
“…However, methods available for the characterization of the subcellular distribution of mineral elements in tissue samples work only semiquantitatively (Schröder et al 1988;Tolstogouzov 1997). However, recent studies (Fritz and Jentschke 1994;Marx et al 1996) using both, EDXS and scanning electron microscopy (SEM), indicated that the usual resolution of conventional microprobe analyses (MA) can be significantly expanded to a resolution much below 1 . Encouraged by these results, we studied our samples also with a transmission electron microscope by quantitative EDXS from selected areas <30nm after calibration with wood tissues of known and Ca compositions.…”
Section: Introductionmentioning
confidence: 99%